Analisis Cerita Rakyat “Putri Pinang Gading” Sebagai Media Eksplorasi Budaya Anak Sekolah Dasar - Richieta Angeline (VisArt: Jurnal Seni Rupa dan Design, 2024)
Indonesia has a very varied cultural richness, reflected in the various cultures, especially the number of folk tales that represent each region. The main problem of this research is that there are many folk tales that are less popular, even forgotten by society due to factors of contemporary development and globalization, one of which is the folk tale "Putri Pinang Gading" from Bangka Belitung. This is very unfortunate because this story contains cultural values, morals and good character to be emulated, especially by girls. The research method used is a qualitative descriptive research method. The problem solving plan is carried out by analyzing why the story is less popular and the suitability of the story as a medium for cultural exploration for children. The main aim of this research is to utilize this story in storybooks or other educational media that not only introduces Bangka Belitung culture, but also introduces more general Indonesian culture and characteristics, such as mutual cooperation and hospitality. The achievements and targets of this design are expected to be a medium for cultural exploration for elementary school students.